Dynamics of T-cell IFN-γ and miR-29a expression during active pulmonary tuberculosis. (30th June 2014) - Afum-Adjei Awuah, Anthony; Ueberberg, Bianca; Owusu-Dabo, Ellis; Frempong, Margaret; Jacobsen, Marc
Abstract : Levels of IFNγ and miR-29a during treatment for active tuberculosis Abstract: IFN-γ is crucial for protection against Mycobacterium tuberculosis . miR-29 was recently shown to non-redundantly inhibit IFN-γ. Here, we investigated IFN-γ and miR-29a expression dynamics of CD4 + T cells from patients during active tuberculosis (TB) ( n = 32) and in household contacts who were latently M. tuberculosis infected ( n = 19) from Ghana. Whereas M. tuberculosis -specific IFN-γ expression was similar during TB chemotherapy, superantigen stimulation indicated generally impaired IFN-γ expression in TB patients. No interdependency between miR-29a and IFN-γ expression of T cells was observed. However, miR-29a was differentially expressed in T cells during chemotherapy. We concluded that differential miR-29a expression in active TB was not causative for impaired IFN-γ expression.